Implementasi Revest Code 4 (RC4) Untuk Data Resep Obat Di RSUP H.Adam Malik - Jaka Prayudha; Oris Krianto Sulaiman; Ita Mariami; Jufri Halim (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Advances in technology will run in accordance with advances in science which will get information easily and quickly. This is supported by information and communication technology which is growing rapidly from year to year. An example is in the management of drug data which is considered very important at H. Adam Malik Hospital. Where the possibility of falsification of drug data and not according to the availability of the number and type according to the needs due to the weakness of the system used. Seeing the existing problems is a consideration for choosing a cryptographic algorithm. Cryptography is based on an information coding algorithm that supports the needs of two aspects of information security, namely the protection of the confidentiality of information data and the protection against falsification of information. Rivest Code 4 (RC4) is one of the methods used to encode text messages in securing drug redemption data for research at H.Adam Malik Hospital. Implementation of Cryptography Implementation in Encoding Drug Redemption Data at H. Adam Malik Hospital Using the Rivest Code 4 (RC4) Method, carried out in two processes, namely the encryption process and the decryption process on the drug redemption data, where the original data (plaintext) entered can be encrypted into encoded data (ciphertext) and can be returned to the original data back as before with the decryption process.